Redesigning local games to stimulate pupils’ interest in learning numeracy in Tanzania - Godfrey, Zitto; Mtebe, Joel (My University, 2018)
The lack of interest and negative attitude in learning mathematics have been described as one of the causes for the continue poor performance of the subject in primary schools and beyond in Tanzania. Despite several government’s efforts to improve pass rate of mathematics, the use of digital games has not been well adopted. This study redesigned local games played by Tanzanian children all over the country into digital games for the aim of stimulating interest of pupils in learning numeracy skills. Three games: Ruka Kamba, Manati, and Kombolela were developed using eXtreme Programming practices and elements of game design for learning proposed by Plass et al. (2015). The developed games were piloted at Mlimani primary school with 111 pupils using direct observation and questionnaire, and 12 teachers using focus group interviews. The study found that the majority of children indicated that developed games are enjoyable, fun, and easy to play. Nonetheless, some few usability problems were identified during observation and are discussed. Similarly, teachers indicated that the developed games were pedagogical effective having content and skills necessary for improving numeracy skills both for self-learning and in the classroom. This study has demonstrated that local games can be redesigned into digital form and be used for stimulating interest of pupils in learning numeracy skills in developing countries
Keywords: Digital games; local games; games for learning; games for Africa; Children games